Menganalisis Pemilihan Model Evaluasi Program Pendidikan - Widiastuti, Widiastuti; Linora, Linora; Hidayat , Hafiz (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to analyze the selection of educational program evaluation models. This research uses a qualitative approach. The research results show that the Scriven Model Scriven designed two evaluation models, namely: (1) Goal-Free Evaluation Approach, and (b) Formative and Summative model, 2) Contenance Evaluation Model (Stake Model). The program evaluation model introduced by Stake is known as the Countenance (overall) model. 3) Alkin Model. Limitations of the evaluation construct as a process of determining the area to be evaluated. 4) CSE-UCLA Evaluation Model. The steps of the CSE-UCLA model are divided into four stages, namely: needs assessment, program planning, formative evaluation, and summative evaluation. 5) Discrepancy Model. The steps in this gap model are: preparation of design, installation, process, d) Measuring the goal (product), e) comparison (program comparison), 6) Brinkerhoff et-al's model consists of: (1) fixed vs emergent evaluation design, (2) formative vs summative evaluation, and (3) experimental and quasi experimental design vs natural/unobtrusive inquiry.